Studying the Effect of Purified Lectin Producing from E. coli on Multidrug Resistance Pantoea Agglomerans - Istabreq Muhammed Ali Salman (Journal of Global Pharma Technology, 2018)
In this study, an isolate of E coli E2 isolated from diarrhea gave the upmost production level of lectin by microscopic glass slide and microtiter plate methods. The results revealed that human erythrocytes O+ gave hem agglutination activities with all E coli isolates and sheep erythrocyte gave hem agglutination activities with all isolates but with lower activity and the isolate coli E2 appeared higher hem agglutination level with O+ blood group by both methods. Purification of the lectin was achieved by45% saturation ammonium sulfate followed by affinity ion-exchange chromatography on DEAE -cellulose column with a yield of 10%, specific activity 754,477 and a purification fold of 6.059. Thirteen isolates of P. agglomerans were isolated from blood specimens from infants patients with blood stream infections and surface swab in neonatal intensive care unit (NICU) in Child’s Central Teaching Hospital in Baghdad ,that showed resistance to cefazolin, cefepime,cefotaxime,gentamicin and ampicillin-sulbactum in different ratio while Purified lectin with concentration 200 µg/ml had antibacterial activity against clinical and environmental bacteria more than other concentration and crud lectin . Keywords: Pantoea agglomerans, Lectin, Antibacterial activity.